The Root Clock as a Signal Integrator System: Ensuring Balance for Survival - Bustillo-Avendaño, Estefano; Serrano-Ron, Laura; Moreno-Risueno, Miguel A. (Frontiers in Plant Science, 2022)
The root system is essential for the survival of terrestrial plants, plant development and adaptation to changing environments. The development of the root system relies on post-embryonic organogenesis, and more specifically on the formation and growth of lateral roots (LR). The spacing of LR along the main root is underpinned by a precise prepatterning mechanism called the Root Clock. In Arabidopsis, the primary output of this mechanism involves the generation of periodic gene expression oscillations in a zone close to the root tip called the Oscillation Zone (OZ). Because of these oscillations, pre-branch sites (PBS) are established in the positions from which LR will emerge, although the oscillations can also possibly regulate the root wavy pattern and growth. Furthermore, we show that the Root Clock is present in LR. In this review, we describe the recent advances unraveling the inner machinery of Root Clock as well as new the new tools to track the Root Clock activity. Moreover, we discuss the basis of how Arabidopsis can balance the creation of a repetitive pattern while integrating both endogenous and exogenous signals to adapt to changing environmental conditions. These signals can work as entrainment signals but in occasions they also affect the periodicity and amplitude of the oscillatory dynamics in gene expression. Finally, we identify similarities with the Segmentation Clock of vertebrates and postulate the existence of a determination front delimiting the end of the oscillations in gene expression and initiating LR organogenesis through the activation of PBS in an ARF7 dependent-manner.